Essential Oil from Lemon (Citrus aurantifolia) Grown in Ben Tre Province, Vietnam: Condition Extraction, Chemical Composition and Antibacterial Properties - To Quyen, Ngo Thi; Ngoc Quyen, Nguyen Thi; Kieu Linh, Huynh Thi; Le Ngoc, Thuy Trang; Tuan Anh, Hoang Le; Khoi Nguyen, Nguyen Hong; Tran, Thien Hien; Thanh Tam, Huynh Ngoc; Cang, Mai Huynh (Asian Journal of Chemistry, 2020)
In present study, a steam distillation method has been adopted for extraction of the essential oil from Vietnamese lemon (Citrus aurantifolia) peel harvested from Tien Giang Province, Vietnam. Various extraction conditions influencing the oil yield were investigated. The resulting essential oil was evaluated for physico-chemical characteristics and antibacterial activities. The chemical composition of oil was investigated by GC-MS. The results showed that with grinded lemon peel, a ratio of water and lemon peels of 3:1 (mL/g), extraction time of 90 min at 120 ºC, the highest essential oil yield was attained at 2.1 %. Bioactive components found at high content included limonene (64.90 %), γ-terpinene (13.70 %), β-pinene (11.89 %), α-pinene (2.11 %), β-cymene (1.80 %) and sabinen (1.52 %). The lemon essential oil in this study was found to inhibit five bacteria strains including Staphylococcus aureus, Bacillus cereus, Escherichia coli, Salmonella enterica and Pseudomonas aeruginosa.